Penerapan Teori Perilaku Informasi Menurut Kulthau di Perpustakaan - Leila Setia Ningsih; Nazmiah Yusdi Arwana; Febrian Elly Sakinah Sari,; Juwita Syahrina; Franindya Purwaningtyas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Information seeking behavior refers to patterns of human behavior related to the nature of information, both in terms of using and seeking information. The term "behavior" refers to how a person obtains information through his behavior. The Kulthau literature review method is used in this paper. According to Kulthau, information seeking behavior has several characteristics, including initiation, which is the initial stage where users are aware of their information needs, selection, where users begin to collect the information topics needed and then look for them through OPAC, browse directly to shelves or by asking users. At this point, the user is confused because he has to decide which information best suits his needs. formulation At this point, the user has determined which information best meets his needs. Users collect information that has been obtained and recorded in books, cellphones, or by taking pictures at this stage, and the last presentation is the user's feelings of satisfaction and dissatisfaction after getting information in the library. Keywords: information seeking behavior, kulthau, library